Neuronavigation in Endonasal Pituitary and Skull Base Surgery Using an Autoregistration Mask without Head Fixation: An Assessment of Accuracy and Practicality - McLaughlin, Nancy; Carrau, Ricardo L.; Kassam, Amin B.; Kelly, Daniel F. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background Intraoperative navigation is an important tool used during endonasal surgery, which typically requires rigid head fixation. Herein we describe a navigational technique using an autoregistration mask without head fixation.Material and Methods Prospective evaluation of a surface autoregistration mask used without rigid head fixation in 12 consecutive endonasal endoscopic skull base procedures was performed with patients positioned in a horseshoe head holder. We assessed the accuracy by recording the surface registration error (SRE) and target registration error (TRE). We also noted the time required for installation and the occurrence of system failure. The system's accuracy was validated using a deep target simultaneously viewed with endoscopic.Results In 12 consecutive endonasal cases performed by a neurosurgeon and ENT team, pathologies included pituitary macroadenomas (9), chordoma (1), craniopharyngioma (1), and sinonasal melanoma (1). Median time required for the registration and accuracy verification was 84 seconds (interval 64 to 129 seconds). The mask stayed on the patient throughout the procedure. The mean SRE was 0.8 mm (interval 0.6 to 0.9 mm). The mean TRE was 0.9 ± 0.7 mm and 1.0 ± 0.8 mm measured respectively at the beginning and end of the case. In every case, the system was judged accurate by the surgical team using the sphenoid keel or an intrasphenoidal bony septation as a deep target for internal validation. No system failure occurred during these 12 cases.Conclusion A facial surface autoregistration mask maintained in place throughout surgery without rigid head fixation allows excellent operational accuracy in endonasal pituitary and skull base surgery. This navigation system is practical, reliable, and noninvasive.
Keywords: endonasal transsphenoidal surgery; navigation; endoscopic surgery; patient positioning; pituitary adenoma; skull base tumor